School Climate as Correlates of Stress Coping Ability, Learning Satisfaction, Self-Efficacy and Social Unrest among Students in University of Benin, Benin City - Olikiabo, Osarentin Samuel; Aideyan, Osarenmwanta Daniel (International Journal of Human Kinetics, Health and Education, 2023)
This study investigated the correlation indices of school climate with stress coping ability, learning satisfaction, self-efficacy and social unrest among undergraduates in the University of Benin, Nigeria. Four hypotheses were formulated. A descriptive correlation research design was used for the study and a population of 420 full time undergraduate students was selected for the study with emphasis on those in their penultimate and final year, using multi-stage sampling technique of stratified, simple, proportionate and purposive sampling techniques, in which 205 and 215 penultimate and final year students were selected respectively. Two sets of self-reported questionnaires were used for data collection. Psychometric properties of the instrument were ascertained for accuracy and reliability. Collected data were analyzed using Pearson Product Moment Correlation at 0.05 level of significance. The findings revealed that stress coping ability, learning satisfaction, self-efficacy and social unrest were positively correlated to school climate. From the values of percentage of variability, school climate account significantly for stress coping ability, learning satisfaction, self-efficacy and social unrest among students in university of Benin. In conclusion, school climate is the framework for effective stress management, motivation to learn and work as well as enhanced interest. Therefore, the need for school management and governing council to promote school climate becomes paramount particularly in enhancing students' overall well-being, fostering a positive cleaning environment, and cultivating a culture of academic excellence and social harmony.